Time-course changes of catabolic proteins following muscle atrophy induced by dexamethasone - Macedo, Anderson G. [UNESP] (2016)
This study was designed to describe the time-course changes of catabolic proteins following muscle atrophy induced by 10 days of dexamethasone (DEX). Rats underwent DEX treatment for 1, 3, 5, 7 and 10 days. Body weight (BW) and lean mass were obtained using a dual energy X-ray absorptiometry (DEXA) scan. Muscle ringer finger1 (MuRF-1), atrogin-1 and myostatin protein levels were analyzed in the tibialis anterior (TA), flexor hallucis longus (FHL) and soleus muscles. DEX treatment reduced lean mass since day-3 and reduced BW since day-5. Specific muscle weight reductions were observed after day-10 in TA (-23%) and after day-5 in FHL (-16%, -17% and -29%, for days 5, 7 and 10, respectively). In TA, myostatin protein level was 36% higher on day-5 and its values were normalized in comparison with controls on day-10. MuRF-1 protein level was increased in TA muscle from day-7 and in FHL muscle only on day-10. This study suggests that DEX-induced muscle atrophy is a dynamic process which involves important signaling factors over time. As demonstrated by DEXA scan, lean mass declines earlier than BW and this response may involve other catabolic proteins than myostatin and MuRF-1. Specifically for TA and FHL, it seems that myostatin may trigger the catabolic process, and MuRF-1 may contribute to maintain muscle atrophy. This information may support any intervention in order to attenuate the muscle atrophy during long period of treatment.